Hyperuricaemia and its association with 10‐year risk of cardiovascular disease among migrant and non‐migrant African populations: the RODAM study. Issue 4 (2nd January 2020) - Chilunga, Felix P.; Henneman, Peter; Requena‐Méndez, Ana; Meeks, Karlijn; Beune, Erik; Mannens, Marcel M. A. M.; Agyemang, Charles
Abstract: Objective: In the advent of rapid urbanisation, migration and epidemiological transition, the extent to which serum uric acid (sUA) affects cardiovascular disease (CVD) risk among Africans is not well understood. We assessed differences in sUA levels and associations with CVD risk among migrant Ghanaians in Europe and non‐migrant Ghanaians in rural and urban Ghana. Methods: Baseline data from 633 rural, 916 urban and 2315 migrant participants (40–70 years) from the cross‐sectional RODAM study were analysed. Hyperuricaemia was defined as sUA >7 mg/dl in men and >6 mg/dl in women. The 10‐year risk of atherosclerotic cardiovascular disease (ASCVD) was calculated using the American College of Cardiology (ACC)/American Heart Association (AHA) risk score which takes into account ethnic minority populations. High CVD risk was defined as ASCVD risk scores ≥7.5%. Logistic regressions were used to assess associations between hyperuricaemia and CVD risk. Results: Prevalence for hyperuricaemia in rural, urban and migrant participants was 17.4%, 19.1% and 31.7% for men, and 15.9%, 18.2% and 33.2% for women, respectively. Hyperuricaemia was positively associated with elevated CVD risk among rural residents (adjusted OR for men 3.28, 95% CI: 1.21–8.96, 6.36, 95% CI: 2.98–13.56 for women), urban residents (1.12, 95% CI: 0.45–2.81 for men, 2.11, 95% CI: 1.26–3.52 for women) and migrants (1.73, 95% CI: 1.01–2.96 for men, 4.61, 95% CI: 3.05–6.97 for women). Conclusion: Our study shows variations of sUA levels in different African contexts. Hyperuricaemia is associated with elevated 10‐year CVD risk in both migrants and non‐migrants. Further studies should identify factors driving associations between sUA and CVD risk in Africans. Abstract : Objectif: Avec l'avènement de l'urbanisation rapide, de la migration et de la transition épidémiologique, la mesure dans laquelle l'acide urique sérique (AUs) affecte le risque de maladie cardiovasculaire (MCV) chez les Africains n'est pas bien comprise. Nous avons évalué les différences dans les niveaux d'AUs et les associations avec le risque de MCV chez les ghanéens migrants en Europe et non migrants dans les zones rurales et urbaines du Ghana. Méthodes: Les données de base de 633 participants ruraux, 916 urbains et 2.315 migrants, de 40 à 70 ans de l'étude transversale RODAM ont été analysées. L'hyperuricémie a été définie comme une AUs > 7 mg/dl chez les hommes et >6 mg/dl chez les femmes. Le risque sur 10 ans de MCV athérosclérosique (MCVAS) a été calculé en utilisant le score de risque de l'American College of Cardiology (ACC)/American Heart Association (AHA) qui prend en compte les populations des minorités ethniques. Un risque de MCV élevé était défini comme un score de risque MCVAS ≥7, 5%. Des régressions logistiques ont été utilisées pour évaluer les associations entre l'hyperuricémie et le risque de MCV. Résultats: La prévalence de l'hyperuricémie chez les participants ruraux, urbains et migrants était de 17, 4% ; 19, 1% et 31, 7% pour les hommes et 15, 9%, 18, 2% et 33, 2% pour les femmes, respectivement. L'hyperuricémie était positivement associée à un risque élevé de MCV chez les résidents ruraux (OR ajusté 3, 28 ; IC95%: 1, 21–8, 96 pour les hommes, 6, 36, IC95%: 2, 98–13, 56 pour les femmes), les résidents urbains (1, 12 ; IC95%: 0, 45–2, 81 pour les hommes, 2, 11 ; IC95%: 1, 26–3, 52 pour les femmes) et les migrants (1, 73 ; IC95%: 1, 01–2, 96 pour les hommes, 4, 61 ; IC95%: 3, 05–6, 97 pour les femmes). Conclusion: Notre étude montre des variations des niveaux d'AUs dans différents contextes africains. L'hyperuricémie est associée à un risque élevé de MCV sur 10 ans chez les migrants et les non‐migrants. Des études plus poussées devraient identifier les facteurs à l'origine des associations entre le risque d'AUs et de MCV chez les africains.